Dampak Media Sosial Terhadap Pengambilan Keputusan Finansial Melalui Pendekatan Kualitatif dalam Industri Keuangan - Budi Harto; Sulistianingsih; Harnavela Sofyan; Taufiq Furqon Nurhakim (KOMVERSAL, 2024)
In today’s digital era, social media has become an integral part of daily life, including in the aspect of financial decision-making. This research aims to analyze the influence of social media on financial decision-making in the financial industry through a qualitative approach. Using case studies and in-depth interviews, this research explores how information presented on social media influences individuals’ financial behavior and decisions. The research involved the participation of various professionals in the financial sector, including analysts, investment managers, and users of financial services. Data analysis was conducted through phenomenological interpretation methods to understand participants’ subjective perceptions, experiences and responses. The findings show that social media plays an important role in shaping financial opinions and decisions, often through narratives and trends that develop on these platforms. The impact is seen in two main aspects: first, the rapid and widespread dissemination of financial information; second, the influence on perceptions of investment risks and opportunities. This research also reveals that social media can provide valuable information, while at the same time posing challenges regarding the accuracy and validity of such information. The results of this study provide new insights into the dynamics between social media and financial decision-making. The findings are useful for financial industry practitioners in developing effective communication and financial education strategies. In addition, this study provides recommendations for policymakers in regulating and monitoring financial content on social media to protect the public interest. Thus, this study makes a significant contribution to the understanding of the interaction between social media and financial decision-making in the digital era.